Ereignis and Da-Sein in the Beiträge zur Philosophie - Schnell, Alexander (2016)
This contribution seeks to clarify the status of Ereignis and Dasein in the Beiträge zur Philosophie and to question, in particular, the relationship between these two concepts. The angle that will be preferred here is that of the discussion with transcendentalism (starting with Kant). The author defends the thesis that there is an alteration in the meaning of " Dasein " between Sein und Zeit and the Beiträge zur Philosophie, having repercussions on the relationship between " Seyn " and " Da-sein " . At the very heart of this new meaning of Da-sein in the Beiträge stands the conception of an " out-standing standing-within " (ausstehendes Innestehen) that must be analyzed in detail.